Use of a Combination Strategy to Improve Morphological and Functional Recovery in Rats With Chronic Spinal Cord Injury - Rodríguez-Barrera, Roxana; Flores-Romero, Adrián; Buzoianu-Anguiano, Vinnitsa; Garcia, Elisa; Soria-Zavala, Karla; Incontri-Abraham, Diego; Garibay-López, Marcela; Juárez-Vignon Whaley, Juan José; Ibarra, Antonio (Frontiers in Neurology, 2020)
Immunization with neural derived peptides (INDP), as well as scar removal (SR) and the use of matrices with bone marrow-mesenchymal stem cells (BMSCs), have been studied separately and proven to induce a functional and morphological improvement after spinal cord injury (SCI). Herein, we evaluated the therapeutic effects of INDP combined with SR and a fibrin glue matrix (FGM) with BMSCs (FGM-BMSCs), on motor recovery, axonal regeneration-associated molecules and cytokine expression, axonal regeneration (catecholaminergic and serotonergic fibers), and the induction of neurogenesis after a chronic SCI. For this purpose, female adult Sprague-Dawley rats were subjected to SCI, sixty days after lesion, rats were randomly distributed in four groups: 1) Rats immunized with complete Freuds adjuvant + PBS (vehicle; PBS-I); 2) Rats with SR+ FGM-BMSCs; 3) Rats with SR+ INDP + FGM-BMSCs; 4) Rats only with INDP. Afterwards, we evaluated motor recovery using the BBB locomotor test. Sixty days after the therapy, protein expression of TNFα, IL-4, IL-10, BDNF and GAP-43 were evaluated using ELISA assay. The number of catecholaminergic and serotonergic fibers were also determined. Neurogenesis was evaluated through immunofluorescence. The results show that INDP when compared to the rest of the groups, significantly increased motor recovery, anti-inflammatory cytokines, axonal regeneration-associated molecules, axonal regeneration, and neurogenesis. The findings observed in this study, suggest that the combination therapy (SR + INDP + FGM-BMSCs) modifies the non-permissive microenvironment post SCI, but it is not capable of inducing an appropriate axonal regeneration or neurogenesis when compared to the treatment with INDP alone.